Ruminal degradability of PREDICAL. Comparison with three forages available during the dry period in Cuba - Stuart, J. R.; La O, O.; Islén, P. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the in situ degradability of PREDICAL (bagasse pith of sugar cane treated with calcium hydroxide and steam) as feed for ruminants, and compare it with the degradability of untreated bagasse pith of sugar cane, star grass (43 d of regrowth), sugar cane and Pennisetum purpureum cv. Cuba CT-115, two experiments of in situ digestibility were performed using a completely randomized design. The time of incubation of the first experiment was 48 h. In the second experiment, treatments were similar and time of incubation was extended up to 72 h. The ruminal degradability of PREDICAL in the second experiment was 58.51 % of the dry matter, and it did not differ from the degradability of a variety of forage sugar cane or the one of Pennisetum purpureum cv. CT-115. The estimation of the metabolizable energy contribution of PREDICAL was 8.58 MJ/kg of dry matter. In situ degradability and ME contribution of PREDICAL were approximately similar regarding those of the sugar cane (Saccharum officinarum L, variety Cuba -1616-75), recommended for forage use. After 72 h of incubation, degradability was similar to that of CT-115 and, in all cases, superior to the one of star grass (Cynodon nlemfuensis) under the typical conditions of dry season. Key words: chemical treatment, bagasse pith, forage, sugar cane